Human dimension of small-scale fisheries and Steller sea lion conflict in Hokkaido coastal water, Japan: exploring perceptions and attitudes between fishermen groups - Brochut, Fleur E. C.; Abe, Nanami; Jimbo, Mina; Tatsuzawa, Shirow; Yamamura, Orio (Frontiers in Marine Science, 2025)
The conflicts between pinnipeds and coastal fisheries are harmful for both pinniped conservation and fishermen’s livelihood. In Hokkaido, Japan, negative interactions between Steller sea lions (SSL) and gillnet and set net fisheries have been an issue for decades. Damage control measures have been implemented, but little is known about fishermen’s perception of the conflict. The recent increase in human dimension research has demonstrated the necessity of this approach in conflict mitigation and resolution. This study aims to clarify the fishermen’s perception of and attitude toward SSL and mitigation methods, and explores the context in which fishermen face this conflict. We conducted 29 on-site interviews with fishermen in several fishing villages along the Sea of Japan and Sea of Okhotsk coasts. We found that most fishermen approved population control as a damage control measure and considered it the only effective method. However, they were open to the development of non-lethal methods. Gillnet and set net fishermen’s perception of SSL's ecological role was more complex than just a threat to their catch. Gillnet fishermen showed a more negative attitude toward SSL compared to set net fishermen. We conclude that fishermen need solutions not only to mitigate the conflict with SSL but also to maintain a decent livelihood while practicing their fishing activity. Our findings explored the larger context surrounding conflict with wildlife and provided valuable information for developing strategies to coexist with wildlife.